Description of the states of two-photon interference in an optical gating Michelson interferometer - Ekkarat Pongophas (2018)
© 2016 Society of Photo-Optical Instrumentation Engineers (SPIE). We investigate the interference of two photons in an optical gating Michelson interferometer. The phenomenon is studied using two different representations of photons: the space-time domain and a step-by-step two-photon state evolution. Both representations lead to identical results. The evolution analysis describes the result by the interference of four two-photon traveling states, whereas the space-time domain analysis reveals that the classical interference of the high-intensity light source is identical to two-photon interference in the quantum regime, except for a multiplicative factor of (n2), where n is the number of photons.